Meta 1. : Die Kunst und ihr Ort. - Baselitz, Georg; Bauer, Ute Meta; Bumiller, Rudolf; Coerper, Andreas; Jahn, Wolf; Obrist, Hans-Ulrich; Straub, René; Verney-Carron, Georges; Walter, Harry; Wulffen, Thomas (Stuttgart : Künstlerhaus Stuttgart, 1992)
Baselitz, Georg ; Bumiller, Rudolf ; Chabrillat, François Joseph ; Coerper, Andreas ; Craig, Stephen ; Fritsch, Katharina ; Gilbert & George ; Oldendorf, Rainer ; Pallanca, Heike ; Schaerf, Eran ; Straub, René ; Walter, Harry
Biografie
Text English-German
boek